Narratives of Homesteading in Times of Crisis: Peasant Economies in the Light of Interwar Polish Diaries - Marta Rakoczy (European Journal of Life Writing, 2025)
This article presents peasant economic ideologies and conceptions examined in the light of interwar Polish diary competitions. Using the tools of Karen Barber’s anthropology of text, I argue that these accounts, partly in defiance of the policy of the time of portraying peasant helplessness and misery, told the story of peasant traditional economic notions tied simultaneously to modern economic ideologies: agrarianism and the cooperative-promoting popular movement. This intertwining of modern and traditional thinking promoted economic concepts and practices forgotten and overlooked by modernization processes, supported by peasants, but also by a socially engaged intelligentsia of bourgeois or landed gentry origin. Peasant economics and economic concepts often avoided extremes: on the one hand, the economic collectivism promised by communist ideologies, and on the other, the liberal individualism associated with the ideology of capitalist laissez-faire. By practicing economic abruptness, they promoted a set of economic virtues forgotten in time of Polish modernization. The description of the process requires a new vocabulary and new historical-anthropological tools.